PERANCANGAN GAME EDUKASI COVID-19 BERBASIS GODOT ENGINE DENGAN METODE MDLC - Roni; Simanjuntak, Pastima (LPPM Universitas Putera Batam, 2022)
Covid-19 virus on 06 August 2021, the number of cases affected by the corona virus was 3,607,863, and on 29 August 2021, the number of cases affected by the corona virus was around 4,213,414, which is about the next 23 days the increase in corona in Indonesia on a large scale and cannot be taken lightly with the corona case. As time goes on, the increasing number of Covid-19 will make it dangerous to infect children, it can be difficult for children to learn about coronavirus through media, social networks, from parents, other people and their environment. As a result, children in their current state are simply anxious, stressed, and upset. So the author wants to make educational games easier to understand, especially for children. The utilization method used is MDLC, with the Godot application it can run the application that the author wants to make. Testing the covid-19 educational game application by utilizing black box testing. Then the programming language used used is GDScript, the design used by the author in this application is limited to problem identification, problem formulation, objectives, data analysis needed, testing application conclusions.